"For me it is always like half an hour": Exploring the acceptable travel time concept in the US and European contexts. (May 2018) - Milakis, Dimitris; van Wee, Bert
Abstract: Milakis et al. (2015b) explored the acceptable travel time concept as a possible factor in the travel and destination decision-making process. These researchers employed both theory and methods triangulation to assess the validity of this concept. Results from interviews with 20 subjects in Berkeley, CA supported the acceptable travel time concept. In this paper, the US study is replicated in Europe (Delft, The Netherlands) to further explore the validity of the acceptable travel time concept, compare results between Delft and Berkeley, and to identify possible factors influencing the acceptable travel time. Results of this study offer support for the validity of the acceptable travel time concept. The subjects in Delft appeared to be less satisfied with longer commute times than the subjects in Berkeley. Urban, transport as well as sociocultural factors might explain this variation in acceptable travel times.